DELAY IN GROWTH HORMONE THERAPY IS NOT DETRIMENTAL - Joshi, Nidhi; Joshi, Harish (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND Pituitary hypothyroidism with growth hormone deficiency is often missed in primary care due to scarce health resources in developing countries. Well-meaning primary care with thyroxine for misdiagnosed primary hypothyroidism may be detrimental. However, the initial use of thyroxine in neonatal central hypothyroidism and growth hormone deficiency prevented long term intellectual decline even when it was inappropriately diagnosed as primary hypothyroidism. CASE Twin male siblings born to second degree consanguineous parents were managed by a pediatric specialist as primary hypothyroidism, requiring unusually high thyroxine doses. T4 was used to guide therapy. After consultation with an endocrinologist, the associated growth hormone deficiency was diagnosed. Pituitary structures on magnetic resonance imaging were normal. The dose of thyroxine was beyond age-matched norms, with free T4 and free T3 values significantly high at 4 years of age. Confirmation of growth hormone deficiency was guided by hormone assay and auxology. Assistance from a growth hormone manufacturing company and government support helped manage both siblings from age 4 up to 18 years, notwithstanding limitations in periodic monitoring. The siblings are now in graduate technical college with respectable height gain. CONCLUSION Appropriate and timely diagnosis of pituitary hypothyroidism and associated growth hormone replacement, even in poor socioeconomic situations, can help nurture productive citizens.